Prevalence and factors associated with comorbid depressive symptoms among people with low back pain in China: A cross-sectional study - He, Chunxia; Chen, Hongxiu; Guo, Ling; Xu, Lisheng; Liu, Qingquan; Zhang, Jiali; Hu, Xiuying (Frontiers in Psychiatry, 2022)
Background: Low back pain is a common medical condition among the general population that is associated with many adverse health effects when comorbid with depressive symptoms. However, little is known about depressive symptoms in the population with low back pain in China. Our study evaluated the prevalence of depressive symptoms and analyzed the factors associated with this condition in the Chinese population with low back pain. Methods: We conducted a cross-sectional analysis of data from the 2018 China Longitudinal Health and Retirement Study. We collected low back pain information for each participant and identified depressive symptoms using the brief version of the Center for Epidemiologic Studies Depression Scale. A wide range of sociodemographic and health-related characteristics of the subjects were extracted. We measured the prevalence of depressive symptoms comorbid with low back pain and analyzed the associated factors by multiple logistic regression. Results: A total of 5779 respondents aged 45 and over with low back pain formed the sample, 41.8% of whom reported depressive symptoms. Multiple logistic regression analysis indicated greater vulnerability to depressive symptoms among females (OR = 1.41, 95% CI, 1.16c1.73), relatively younger persons (60–74 years: OR = 0.72, 95% CI, 0.63–0.83; ≥75 years: OR = 0.62, 95% CI, 0.49–0.79, reference: 45–59 years), those from the central and western regions (central: OR = 1.39, 95% CI, 1.18–1.64; western: OR = 1.56, 95% CI, 1.33–1.83), participants with extremely short sleep duration (OR = 2.74, 95% CI, 2.33–3.23), those with poor self-perceived health status (OR = 2.91, 95% CI, 2.34–3.63,),multisite pain (OR=1.54, 95%CI, 1.20–1.98) and disability in activities of daily living disability (Basic: OR =1.70, 95% CI, 1.47–1.98; Instrumental: OR = 1.95, 95% CI, 1.70–2.24). Conclusion: Depressive symptoms were highly prevalent in the Chinese population≥45 years with low back pain. More attention should be paid to the individuals at high-risk confirmed by this study to facilitate early identification and intervention against depressive symptoms.